Tradução, adaptação e validação do questionário Fantastic Lifestyle Assessment em estudantes do ensino superior - Silva, Armando Manuel (2014)
The scope of this study was to make the translation, cultural adaptation and validation of the Fantastic Lifestyle Assessment questionnaire in a group of students in higher education in Portugal. The process of translation and validation consisted of translation, back translation, expert committee review, pre-testing and testing of the psychometric properties. The final version adapted with 30 questions was applied to a sample of 707 university students. The results showed that the instrument demonstrated good overall internal consistency for an instrument used to measure a latent variable. When the items were grouped into domains, it was found that they all contributed equally to the stability of the instrument. The reproducibility assessed by intraclass correlation was high. Construct validity tested by the classification capacity of the instrument in four, three and two categories was 67.6%, 67.6% and 100%, with a Kappa index of 0.55, 0.55 and 1.00, respectively. The concurrent validity was also evaluated by correlating it with “My Lifestyle,” namely another instrument measuring the same construct. The conclusion was that the Fantastic Lifestyle Assessment, is a reliable and valid instrument for lifestyle assessment in young adults.